Massive amplification of photoluminescence and exceptional water stability of MAPbBr3 nanocrystals through core–shell nanostructure formation in a self-defence mechanism. Issue 19 (10th August 2022) - Chatterjee, Shovon; Khan, Tanmoy; Sen, Arghya; Das, Nilimesh; Sen, Pratik
Abstract : Vulnerability to atmospheric conditions and their associated toxicity limit the practical/industrial use of perovskites despite their tremendous promise in optoelectronics. Abstract : Vulnerability to atmospheric conditions and their associated toxicity limit the practical/industrial use of perovskites despite their tremendous promise in optoelectronics. This study utilized an ionic liquid-like solvent to synthesize methylammonium lead bromide (MAPbBr3 ) nanocrystals (NCs). The synthesized NCs showed a moderate photoluminescence quantum yield (PLQY) of ∼19% and high environmental stability of at least six months. Further, the entire visible range was tuned through the anion-exchange method. More interestingly, the synthesized NCs formed a core–shell structure in a unique self-defence mechanism in the presence of water, which was proposed to be MAPbBr3 @lead laurate. This core–shell structure was found to be beneficial for (a) preventing further degradation of the NC, and making it water stable (at least for two months), (b) improving the PLQY by surface modification inducing a massive five-fold amplification, and (c) restricting the anion-exchange reaction. Moreover, these unique properties were achieved without any special control. Moreover, the successful synthesis of other MAPbX3 (X = Cl, I) demonstrated its potential applicability.